Passifloraceae endémicas del Perú - León, Blanca (2006)
The Passifloraceae are represented in Peru by three genera and 95 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mainly vines and lianas. Here we recognize as Peruvian endemics 24 species and seven infra-specific taxa, all in the genus Passiflora. These endemic taxa are found mainly in Very Humid Montane and Very Humid Premontane Forests regions, between 700 and 2850 m elevation. Five endemic taxa are recorded in the Peruvian System of Protected Natural Areas.